A post-implementation evaluation method for enterprise architecture / Fatemeh Nikpay - Fatemeh, Nikpay (2017)
Enterprise Architecture (EA) is a strategy that is commonly used to improve the alignment of business and Information Technology (IT) within an enterprise. Implementing an EA is a sophisticated, lengthy, and costly process which tends to face serious failure. Thus, it is essential to perform a successful and thorough evaluation at the post-implementation stage of an EA project to evaluate how much the developed Information Systems (ISs) and IT solutions have succeeded in achieving its predetermined objectives and improving the integration and stability of enterprise. Most existing evaluation models do not provide structured and comprehensive way to cover EA implementation aspects. As a consequence, EA projects may face inadequate adaptation for future changes, lack of structured guideline for evaluating the EA artefacts, and lack of structured practices for continual improvement of EA implementation. Moreover, without having structured and theory-based model for evaluating EA artefacts, the enterprise decision makers cannot achieve the targeted goals of EA implementation project, and they may waste time and budget. To address the issues, this thesis proposes the post implemented method to assist the implemented EA within the enterprise, which combine solid theory and good practices. Moreover, the proposed method focuses on two important dimensions which are crucial functionality and effectiveness. This thesis has gone through three phases: preparation, development, and evaluation. The first phase provides the foundations and requirements of the proposed method based on Systematic Literature Review (SLR) and interviews with EA practitioners for the required practices and factors that affect the EA implementation evaluation. The second phase focuses on the development of the method for EA implementation evaluation. Moreover, the basis for the proposed method are the program theory and IS Evaluation Theory using design science approach. Finally, the proposed method is validated by means of two case studies, cross case analysis and expert reviews. Accumulated results from the evaluation reveals that the proposed method is usable and effective and it has the capability to facilitate the success of EA projects.